Hubungan antara Pola Asuh Orangtua dengan Kemampuan Pemahaman Kosakata pada Anak Disabilitas Intelektual di SLB Surakarta - Adrisel, Deanikha; Tirtawati, Dewi (Jurnal Terapi Wicara dan Bahasa, 2023)
Background: Parenting style is one factor supporting the achievement of children's speech and language development according to their age stages because proper parenting is very important so that children can have good growth. The family is the first container that influences the development of children's vocabulary comprehension abilities. Parenting style is closely related to the development of vocabulary comprehension skills in children, the better the parenting style, the better the child's ability to understand vocabulary. Purpose: This study aims to determine whether there is a relationship between parenting styles and the ability to understand vocabulary in children with intellectual disabilities in SLB Surakarta. Methods: Research using quantitative research with a cross sectional approach. The population of this study were children with intellectual disabilities at SLB Surakarta. The sampling technique was carried out by purposive sampling. The number of respondents in this study were 30 respondents. Data analysis was carried out by using descriptive and bivariate statistical analysis tests. Spearman Rank's test is used for bivariate analysis. Results: The results of the analysis test with Spearman Rank's found a relationship between parenting styles and the ability to understand vocabulary. It is proven based on the analysis of the data obtained a significance of 0.001 where if it is less than 0.05 then Ha (alternative hypothesis) is accepted and the correlation coefficient (r) was -0.683. Conclusion: There is a relationship between parenting style and the ability to understand vocabulary in children with intellectual disabilities in SLB Surakarta. Keywords: Parenting Patterns, Vocabulary Comprehension Ability, Children with Intellectual Disabilities